Analysis Of Physical Condition Test Results Of Karate Athletes In PPLP Athletes Of Gorontalo Province In 2024 And 2025 - Siregar, Nurkhoiroh; Meriharyani; Safri Irawan; Agung Prasetyo; Octa Serka Yudha (Journal Physical Health Recreation (JPHR), 2025)
The recommendation of this study is to determine the differences in the results of physical condition tests focused on karate kata and kumite athletes of PPLP Gorontalo Province and to determine the percentage of participants in the physical condition test of karate kata and kumite athletes of PPLP Gorontalo Province. In addition, this study is an evaluation of the results of karate kata and kumite tests each year from 2024 to 2025. This study shows the results of the physical tests of male and female karate athletes kata and kumite PPLP Gorontalo Province in 2024 - 2025 PPLP Gorontalo Province, namely the Bleep test in 2024-2025 experienced an average increase of 0.12%. The 20-meter running test in 2024 to 2025 experienced an average increase of 1.27%. The 300m running test in 2024-2025 experienced an average increase of 82.72%, the Push up Test in 2024-2025 experienced an average increase of 75%. The 2024-2025 Sit Up Test experienced an average increase of 14.41%, while the physical test results of male karate athletes in the kata and kumite categories of PPLP Gorontalo Province athletes in 2024-2025, namely the 2024-2025 Bleep Test, experienced an average decrease of 4.35%. , The 20-meter running test from 2024 to 2025 experienced an average increase of 2.78%, the 300m running test from 2024-2025 experienced an average increase of 8.16%, the Push-up test from 2024-2025 experienced an average increase of 28.67%, the Sit-up test from 2024-2025 remained at an average of 26.40%, So that there was a change in the results of the physical condition test of the PPLP Gorontalo Province in 2024 - 2025 PPLP Gorontalo Province. The most prominent changes in the test results were in the results of the 20m running test, Bleep test, 300m running, Sit-up and Push-up